Avaliação dos procedimentos de higienização dos brinquedos infantis e das brinquedotecas nacionais - Chadi, Paula Fernades [UNESP] (2014)
The humanization policies attempt to enable health professionals to ease the hostility of the hospital with the child living objects, such as their favorite toy. This measure has been cautious since the release of Toy entering the hospital needs investigation in relation to the risks of transmission of microorganisms, the nature of the material it is made the toy and, consequently, it is capable of cleaning and disinfecting . Despite its great importance, the toy / therapeutic play, can be a vehicle of transmission of microorganisms in unit recreation. The aim of this study was to evaluate the cleaning procedures of the national children's toys and playrooms. This is a quantitative study among nurses members of the Brazilian Society of Pediatrics and Neonatal Nurses who work in pediatrics in the hospital. The sample consisted of 30 nurses, 17 of which were tied to area hospitals, one ambulatory area and 12 to basic health care. Being 13 hospitals possess playrooms. As the dominance of the composition of toys predominated in plastic. About the product hygiene only one of this item that nurses respond do the cleaning with soap and water followed by 70% alcohol to. Conclueds needs further investigations with larger number of participants to have a standard of hygienic methods in accordance with the composition of the toy in the hospital environment.